Digitalization and Innovation System Information As Driver Growth Economy - Caryssa Putri; Muhammd Irwan Padli Nasution (Young Journal of Social Sciences and Humanities, 2025)
Digital transformation not only enables businesses to improve operational efficiency but also boosts productivity through process optimization and the use of data-driven technologies. By implementing innovative information systems, such as e-commerce, fintech, big data, and artificial intelligence, organizations are able to increase the added value of products and services and strengthen their competitive position in the global market. Furthermore, digitalization enables faster, more informed decision-making, increases operational transparency, and reduces costs. This study aims to explore how digitalization and information systems innovation contribute to accelerating contemporary economic growth, with a particular focus on emerging challenges in developing countries. Some of the issues identified include technological infrastructure readiness, digital access inequality, cybersecurity, and risk management related to the adoption of new technologies. The results show that organizations that are able to effectively integrate information systems innovation with their business strategies will gain a significant competitive advantage, while those that fail to adapt risk being left behind in global competition. The study concludes that digitalization is not simply a technical tool but also a strategic factor that drives economic growth, innovation, and efficiency, while also requiring careful planning to address the inherent risks and challenges. This understanding is important for designing business policies and strategies that can optimally utilize modern technological opportunities.